2004
DOI: 10.1523/jneurosci.2713-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Opening of T-Type Ca2+Channels Contributes to the Irregular Firing of Dopamine Neurons in Neonatal Rats

Abstract: During early postnatal development, midbrain dopamine (DA) neurons display anomalous firing patterns and amphetamine response. Spontaneous miniature hyperpolarizations (SMHs) are observed in DA neurons during the same period but not in adults. These hyperpolarizations have been shown to be dependent on the release of Ca 2ϩ from internal stores and the subsequent activation of Ca 2ϩ -sensitive K ϩ channels. However, the triggering mechanism and the functional significance of SMHs remain poorly understood. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 69 publications
7
74
1
Order By: Relevance
“…Therefore, IP 3 tone produced by sustained receptor activation likely affects the entire pool of Ca 2ϩ stores. In line with this, our previous study has demonstrated that sustained activation of ␣1ARs suppresses RyR-mediated spontaneous Ca 2ϩ responses observed in DA neurons of neonatal rats (Cui et al, 2004).…”
Section: Ip 3 Mediates Differential Regulationsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, IP 3 tone produced by sustained receptor activation likely affects the entire pool of Ca 2ϩ stores. In line with this, our previous study has demonstrated that sustained activation of ␣1ARs suppresses RyR-mediated spontaneous Ca 2ϩ responses observed in DA neurons of neonatal rats (Cui et al, 2004).…”
Section: Ip 3 Mediates Differential Regulationsupporting
confidence: 78%
“…Horizontal slices (200 -220 m) of the ventral midbrain were prepared from adult Sprague Dawley rats (3-6 weeks old), as described previously (Cui et al, 2004). Slices were maintained at 35°C and perfused at a rate of 2-3 ml/min with physiological saline containing the following (in mM): 126 NaCl, 2.5 KCl, 1.2 NaH 2 PO 4 , 1.2 MgCl 2 , 2.4 CaCl 2 , 11 glucose, 21.4 NaHCO 3 , saturated with 95% O 2 and 5% CO 2 , pH 7.4, 300 mOsm/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LVA Ca 2ϩ channels do not appear to be coupled to CICR in the dLGN (Budde et al, 2000), these channels are coupled to CICR via caffeine-sensitive ryanodine receptors in midbrain dopaminergic neurons in neonatal rats (Cui et al, 2004). Our finding that LVA Ca 2ϩ channels are coupled functionally to CICR in the PVT suggests that LVA Ca 2ϩ channels may be coupled differentially to Ca 2ϩ -dependent intracellular signaling systems in different regions of the thalamus.…”
Section: Discussionmentioning
confidence: 69%
“…To address these questions, we applied nimodipine at 10 M as a blocker for the L type of channels (Castillo et al, 1994;Kapur et al, 1998), and NiCl 2 at 100 M as a blocker for the T type of channels (Fox et al, 1987;Komatsu and Iwakiri, 1992). Because this concentration of Ni 2ϩ might not selectively block the T type of channels, we also used mibefradil dihydrochloride at 100 M (Martin et al, 2000;Cui et al, 2004) as another blocker for T type channels. We did not systematically examine blockers for the N and P/Q types of Ca 2ϩ channels, because these channels are reported to operate primarily in presynaptic sites (Wu and Saggau, 1994;Qian and Noebels, 2001) and, thus, the application of blockers for these channels are expected to block synaptic transmission itself.…”
Section: Ltp Of Excitatory Synapses On Fs-gaba Neurons Is Not Dependementioning
confidence: 99%